15.7k views
25 votes
Y + 3x = -1
y = 1/2x+ 20

User Robin Raju
by
6.0k points

2 Answers

6 votes
im not sure if it’s right but I think it’s -6,17
User PilouPili
by
5.2k points
5 votes
So you can substitute equation 2 in equation 1.

U believe your equation 2 should read y= x/2 + 20 (the x is next to the 1 and not to the 2, right)

So after substituting, we have:

(x/2)+20+3x = -1

Multiply the whole equation by 2:

x + 40 + 6x = -2
7x = -2-40
7x = -42
x = -6

Replace x=-6 in equation 1:

y + 3(-6) = -1
y - 18 = -1
y =17
User MADMap
by
5.6k points